Single-session associative protocol for dentin hypersensitivity management: a 1-year randomized, blinded clinical study - Thayna Carolina Zeni; Poliana Maria de Faveri Cardoso; Rafael da Silva Vanolli; Márcio José Mendonça; Julio Katuhide Ueda; Veridiana Camilotti (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to establish a single-session associative protocol for non-restorative management of dentin hypersensitivity (DH).Materials and MethodsTwenty-four individuals with DH and a minimum sensitivity level of 4 on the visual analog scale (VAS) were selected. The study was conducted in a split-mouth design, with each participant (n = 20) having at least 1 affected tooth in all quadrants. The management protocols consisted of control group: universal adhesive, Neural Desensitizing Protocol group: 5% potassium nitrate, Mixed Desensitizing Protocol (PAM) group: 5% sodium fluoride and 5% potassium nitrate, Remineralizing Desensitizing Protocol (PDR) group: surface-partially reacted glass technology photopolymerizable varnish. Evaluations were performed immediately after application, at 1 week, 1 month, 2 months, and 12 months using the VAS sensitivity test.ResultsThe scores were subjected to statistical analysis using the Friedman test (p < 0.05), Durbin-Conover test (p < 0.05), and Wilcoxon test (p < 0.05). At the 12-month evaluation, all groups showed statistically significant differences compared to the initial assessment. For the evaluation after 12 months, there was a statistically significant difference between the PAM group, the control group, and the PDR group.ConclusionsIt can be concluded that all groups were effective in controlling DH, but there were significant results in the control group and PDR group. The clinical relevance of this study is to demonstrate that the application of single-session desensitizing protocols can be effective in controlling DH for up to 12 months.Trial RegistrationBrazilian Clinical Trials Registry Identifier: RBR-4r63d7s